2020
DOI: 10.1038/s41598-020-72597-0
|View full text |Cite
|
Sign up to set email alerts
|

There is a cycle to cycle variation in ovarian response and pre-hCG serum progesterone level: an analysis of 244 consecutive IVF cycles

Abstract: We aimed to answer one key question, that was not previously addressed as to whether serum progesterone (P4-hCG day) and its co-variates (estradiol (E2-hCG day) and the number of retrieved oocytes) of a given cycle can be predictive of the subsequent cycle when both cycles are consecutive and comparable for the stimulation protocol, gonadotropin dose and duration of stimulation. We analyzed such 244 consecutive (< 6 months) IVF cycles in 122 patients with GnRH agonist long protocol and found that P4, E2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(39 reference statements)
0
2
1
Order By: Relevance
“…The authors observed certain GAST response cycle variability in some of the patients and argued that the fluctuation can only be attributed to chance variation. However, in contrast to their conclusion, it was shown that there is some cycle to cycle variation of hormonal variables and oocyte yield 20 not explained by baseline AFC and AMH 21 which may attribute to GAST individual cycle results.…”
Section: Discussioncontrasting
confidence: 68%
“…The authors observed certain GAST response cycle variability in some of the patients and argued that the fluctuation can only be attributed to chance variation. However, in contrast to their conclusion, it was shown that there is some cycle to cycle variation of hormonal variables and oocyte yield 20 not explained by baseline AFC and AMH 21 which may attribute to GAST individual cycle results.…”
Section: Discussioncontrasting
confidence: 68%
“…We must point out that cycle-to-cycle variation in ovarian response exists and that the growth and steroidogenic characteristics of antral cohorts in response to exogenous FSH may vary from one cycle to another (e.g. expression and sensitivity of FSH receptors of granulosa cells ( 49 )). However, the cycle-to-cycle heterogeneity would probably be similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, for the subset of patients with prior retrievals, we tried using prior outcomes as an input to our nearest-neighbor model but found that this did not meaningfully change the dose curves or expected benefit analysis. This is possibly due to the cycle-to-cycle variation in outcomes that exists even when using the same dose of gonadotropins (Yildiz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%